ARID3B silencing inhibits E2F-mediated transcription and cell proliferation - A. S. M. Saadat, Khandakar; Lestari, Widya; Teng, Ma; Pratama, Endrawan; Ohtani, Kiyoshi; Ikeda, Masa-Aki (2013)
ARID3B is a member of ARID3 (AT-rich interacting domain) family of DNA-binding proteins, and overexpressed in human malignant tumors. The closely related family member, ARID3A, was isolated as a protein binding to E2F1 transcription factor and activates E2F-dependent transcription. However, the function of ARID3B in the regulation of E2F-responsive genes remains largely unknown. Here, we show that siRNA-mediated gene silncing of ARID3B blocked transcription of E2F-responsive genes, such as E2F1,p107,cyclin E1, CDC2 and CDC6 in normal human dermal fibroblast (NHDFs). Ectopic overexpression of ARID3B up-regulated transcription of these E2F-responsive genes in quisencet NHDFs. Furthermore, the inhibition of cyclin E1 expression by ARId3B silencing was not restored by E2F1. We found putative ARID3-binding sites in the E2F-responsive genes and show that ARID3A and ARID3B were recruited to these sites in vivo. Mutation of putative ARID3-binding sites reduced the CDC promoter activity in both serum-starved and stimulated conditions. Finally, ARID3B silencing attenuated S phase entry of NHDFs, and suppressed tumor cell growth. These results indicate that ARID3B play an important role for E2F-meditaed transcriptional activation and cell proliferation.